Assessing the risk of COVID-19 in Feed the Future countries - Koo, Jawoo; Azzarri, Carlo; Ghosh, Aniruddha; Quabili, Wahid (International Food Policy Research Institute, 2021)
In anticipation of the development of a safe and effective COVID-19 vaccine—the distribution of which will be a complex and sensitive issue—governments will need to assess the number and location of the most vulnerable people within their populations. Problematically, however, tracking data for most low- and middle-income countries are only available at the national level. The most widely used dataset by the Johns Hopkins University Center for Systems Science and Engineering (Dong, Du, and Gardner 2020), for example, does not include subnational data for Feed the Future’s 12 target countries in Africa south of the Sahara (SSA) and South Asia: Bangladesh, Ethiopia, Ghana, Guatemala, Honduras, Kenya, Nepal, Niger, Nigeria, Mali, Senegal, and Uganda. For this reason, the Gender, Climate Change, and Nutrition Integration Initiative (GCAN) was commissioned to correlate Demographic and Health Survey data from the United States Agency for International Development (USAID) with geospatial data in order to develop a subnational dataset of key COVID-19 risk indicators based on which potential risk hotspots were identified. This summarizes the study’s analysis in the 12 Feed the Future countries and across subnational administrative units within each country.